2018
DOI: 10.1155/2018/5163472
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Analysis of Ancient Timber Architecture by Considering the Correlation of Different Failure Modes

Abstract: The paper proposes an innovative method of analyzing the seismic fragility of ancient timber architecture. The method is based on the Copulas, in which correlation between different failure modes is considered. This method is applied to assess the vulnerability of ancient timber architecture in Ming dynasty. The assessment includes four steps. In the first step, the incremental dynamic analysis is employed to establish seismic vulnerability curves of different failure modes for the structure. After that, Copul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Xie et al [18] studied the static behaviour of a twotiered Dou-Gong system reinforced with super-elastic alloy, and found that the pre-strain of the super-elastic alloy can significantly increase the damping ratio in the structure. Previous studies [19][20][21][22] tried to evaluate the mechanical properties and safety state of an entire timber structure through finite element modelling, mathematical methods, and a shaking-table test. However, all of these studies focused on the timer components and timber frames without considering the infill walls.…”
Section: History and Research Of Chinese Traditional Structuresmentioning
confidence: 99%
“…Xie et al [18] studied the static behaviour of a twotiered Dou-Gong system reinforced with super-elastic alloy, and found that the pre-strain of the super-elastic alloy can significantly increase the damping ratio in the structure. Previous studies [19][20][21][22] tried to evaluate the mechanical properties and safety state of an entire timber structure through finite element modelling, mathematical methods, and a shaking-table test. However, all of these studies focused on the timer components and timber frames without considering the infill walls.…”
Section: History and Research Of Chinese Traditional Structuresmentioning
confidence: 99%
“…A simplified hybrid method has been presented for nonlinear FEM, particularly for timber frame buildings, such that the elements are modelled using the experimental testing results from the substructures [100]. Hybrid simulation has been utilized to investigate the seismic vulnerability of timber frame buildings [101][102][103][104][105][106][107][108][109], and then developed for numerical simulation of log houses [110][111][112][113][114][115] and post and beam structures [116][117][118][119][120][121].…”
Section: Seismic Vulnerability Assessmentmentioning
confidence: 99%
“…22 evaluation indexes are selected in this paper, which are shown in Figure 1. Attribute measure functions of single indexes can be built by equations (4)- (6). And x 2 , x 2 ′ , y 3 , d 2 , and q 3 are Table 10.…”
Section: Attribute Measure Function Of Single Indexesmentioning
confidence: 99%
“…Has penetrating cracks that greatly affect mechanical properties q 1 is the weathering depth; H is the height of the wall; B is the thickness of the wall. 6 Advances in Civil Engineering Table 10: Attribute measurement functions for single index.…”
Section: Calculation Of Weights Of Evaluation Indexesmentioning
confidence: 99%
See 1 more Smart Citation